2008
DOI: 10.1016/j.juro.2008.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Early Continence After Reconstruction of the Periprostatic Tissues in Patients Undergoing Computer Assisted (Robotic) Prostatectomy: Results of a 2 Group Parallel Randomized Controlled Trial

Abstract: Early urinary continence rates were high in patients undergoing single or double layer urethrovesical anastomosis. We found no improvement in early continence rates with reconstruction of the periprostatic tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
5
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(139 citation statements)
references
References 19 publications
2
129
5
3
Order By: Relevance
“…Secondly, at the beginning of the vesicourethral anastomosis, the bladder wall was stitched 1-2 cm dorsocephalad to the bladder neck (at positions 1 and 11 o'clock on the bladder neck) and the musculofascial plate was stitched at 5 and 7 o'clock positions on the urethra instead of using Rocco's second-layer stitch. Although it was previously reported that urinary continence was not improved by PMPR (14), in the present study we demonstrated that urinary continence was recovered significantly earlier in patients undergoing LRPs with our modified PMPR. We also evaluated the postoperative cystograms and compared the bladder shapes between patients undergoing LRP with PMPR and those undergoing LRP without PMPR.…”
Section: Introductioncontrasting
confidence: 76%
“…Secondly, at the beginning of the vesicourethral anastomosis, the bladder wall was stitched 1-2 cm dorsocephalad to the bladder neck (at positions 1 and 11 o'clock on the bladder neck) and the musculofascial plate was stitched at 5 and 7 o'clock positions on the urethra instead of using Rocco's second-layer stitch. Although it was previously reported that urinary continence was not improved by PMPR (14), in the present study we demonstrated that urinary continence was recovered significantly earlier in patients undergoing LRPs with our modified PMPR. We also evaluated the postoperative cystograms and compared the bladder shapes between patients undergoing LRP with PMPR and those undergoing LRP without PMPR.…”
Section: Introductioncontrasting
confidence: 76%
“…1 Late post-prostatectomy continence rates in expert hands are high (76-92%) 2, 3 ; however, early continence rates are routinely lower and vary widely (32-84%). 2,4 Efforts to improve post-prostatectomy continence include maximizing urethral length, 5 using nerve-sparing techniques, 6 and preserving or recreating urethral support through reconstructive techniques. 2,[7][8][9][10] The use of a sling for suspension of the vesicourethral anastomosis at the time of prostatectomy has shown early promise, but has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…First, we did not investigate functional outcomes and perioperative complication rates associated with the three surgical techniques. However, this has been the subject of previous studies and was not the primary goal of the present study [21][22][23]. Second, follow-up for biochemical outcome was limited; extended follow-up was not available because of the relatively newer utilization of RARP for treatment of prostate cancer compared to RRP.…”
Section: Discussionmentioning
confidence: 97%